Preparation method of ultrahigh-capacity positive electrode lithium supplementing agent

Preparation of positive electrode lithium supplement agent by mixing the specified ratio of lithium source and transition metal compounds and high-temperature sintering, solving the irreversible capacity loss and residue problems of lithium-ion batteries, achieving high-capacity and low-residue positive electrode lithium supplement agent, and improving lithium ions Cycle stability and energy density of the battery.

CN119252921APending Publication Date: 2025-01-03GUANGZHOU BOYUE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411366107.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing lithium-ion batteries form solid electrolyte interface during the first charging process, resulting in irreversible capacity loss, especially the irreversible capacity loss of silicon-based and tin-based negative electrodes, which reduces the energy density of the battery. The existing theory of positive electrode lithium supplementation agent The specific capacity is less than 1000mAh/g and the residual transition metal oxide affects the health of the battery.

Method used

Ultra-high capacity positive electrode lithium supplement agent is prepared by mixing the specified ratio of lithium source and transition metal compounds, high-speed mixing, high-temperature sintering and ball milling under an inert atmosphere, and the utilization rate of lithium ions is improved through the placeholding and catalytic action of transition metals and reducing deliquification electricity. , reducing residue amount.

Benefits of technology

The first charging capacity exceeds 1000mAh/g, which reduces the amount of lithium supplement agent added and residues, improves the cycle stability and energy density of lithium-ion batteries, and reduces side reactions on the electrode surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252921A_ABST
    Figure CN119252921A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: mixing: uniformly mixing a lithium source and a transition metal compound MO at a high speed in an inert atmosphere according to a specified proportion to obtain an initial mixed material; sintering: placing the initial mixed material in an inert atmosphere for high-temperature sintering to obtain a sintered material; and performing ball milling, namely performing ball milling on the sintered material to obtain the positive electrode lithium supplementing agent. The mixing ratio of the lithium source to the transition metal compound is determined according to the molar ratio of Li in the lithium source to transition metal M in the transition metal compound. The invention discloses an ultrahigh-capacity positive electrode lithium supplement agent and a preparation method thereof, in an inert atmosphere, a lithium source and a transition metal compound are taken as precursors, the ultrahigh-capacity positive electrode lithium supplement agent is prepared through a simple solid-phase mixing, sintering and crushing process, the lithium supplement agent can provide lithium supplement capacity exceeding 1000mAh / g, residues are few after formation, and the preparation method is simple and easy to implement. The influence on the energy density of the lithium battery and the electrode surface interface stability is small. By adding a small amount of the ultrahigh-capacity positive electrode lithium supplement agent, the cycle stability of the lithium ion battery can be effectively improved, and the cycle life of a battery cell is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium ion batteries, and in particular to a method for preparing an ultra-high capacity positive electrode lithium supplement. Background Art

[0002] With the development of technology, lithium-ion batteries play an indispensable role in our lives. Many studies have shown that in lithium-ion batteries, the first charging process will form a solid electrolyte interface (SEI) on the surface of the negative electrode, which will consume the active lithium in the positive electrode and cause irreversible capacity loss. At present, the irreversible capacity loss of the widely used graphite negative electrode can reach about 10%, while for silicon-based and tin-based negative electrodes with high specific capacity, the irreversible capacity loss is even as high as 30% or more, which significantly reduces the energy density of lithium-ion batteries.

[0003] To solve this problem, the battery needs to be replenished with lithium in the initial stage. Lithium replenishment is a method of pre-storing lithium ions in the positive or negative electrode of the battery to compensate for the irreversible capacity loss during the first charge and discharge process, thereby improving the capacity and cycle performance of the battery. Positive electrode lithium replenishment has the advantages of simple process, low price and high safety, and has received widespread attention in recent years.

[0004] The existing commercially mature ternary positive electrode lithium supplements include lithium-rich nickel-based lithium, lithium-rich iron-based lithium, and lithium-rich cobalt-based lithium. Some patented technologies also propose methods for preparing multi-element positive electrode lithium supplements, such as patent CN114050258A, which proposes a positive electrode lithium supplement Li 5 FeMbO 4 The preparation method uses Fe as the central element of the lithium supplement, and distributes multiple elements such as Ni, Co, and Mn at the same time. The first charging capacity of this product is about 500mAh / g. However, the theoretical specific capacity of the above lithium supplements is less than 1000mAh / g, and 1%-5% of the lithium supplement needs to be mixed in the positive electrode, and a large amount of transition metal oxides remain after the first charge and delithiation. This residue not only reduces the energy density of the battery, but also increases the side reactions on the electrode surface, affecting the health of the battery cell. Therefore, a method for preparing a positive electrode lithium supplement with ultra-high capacity and low residue is needed. Summary of the invention

[0005] In view of the above problems, the present invention aims to provide a method for preparing an ultra-high capacity positive electrode lithium supplement.

[0006] To achieve the technical purpose, the scheme of the present invention is: a method for preparing an ultra-high capacity positive electrode lithium supplement, comprising the following steps:

[0007] S1, mixing, mixing the lithium source and the transition metal compound MO at a high speed in an inert atmosphere in a specified ratio to obtain an initial mixed material;

[0008] S2, sintering, placing the initial mixed material in an inert atmosphere for high-temperature sintering to obtain a sintered material;

[0009] S3, ball milling, ball milling the sintered material to obtain a positive electrode lithium supplement.

[0010] Preferably, the mixing ratio of the lithium source and the transition metal compound is determined according to the molar ratio of Li in the lithium source and the transition metal M in the transition metal compound, and the molar ratio of Li to the transition metal M is in the range of Li:M=9-25.

[0011] Preferably, the lithium source is Li 2 O、LiOH·H 2 O. Li 2 CO 3 、LiNO 3 , Li 2 C 2 O 4 one or more combinations of.

[0012] Preferably, M in the transition metal compound is a combination of one or more of Fe, Co, Ni, Mn, Cu and Ti.

[0013] Preferably, the transition metal compound MO is Li 5 FeO 4 , Li 2 NiO 2 , Li 6 CoO 4 ,FeO,Fe 2 O 3 , Fe 3 O 4 、Co 3 O 4 、Co 2 O 3 、MnO、MnO 2 、NiO、TiO 2 A combination of one or more of .

[0014] Preferably, the transition metal compound MO is nanoscale, and the particle size of the transition metal compound MO is less than 80 nm.

[0015] Preferably, the inert gas in steps S1 and S2 is Ar, N 2 、A combination of one or more of He.

[0016] Preferably, in step S1, a high-speed mixer is used for high-speed mixing operation, the rotation speed of the high-speed mixer is 1500-2500 rpm, and the mixing time is 60-120 min.

[0017] Preferably, in step S2, the high temperature sintering temperature is 450-1000° C., and the sintering time is 5-20 hours.

[0018] Preferably, in step S1, a ball mill is used for ball milling, the ratio of ball milling beads to sintering material in the ball mill is 5:1-20:1; the rotation speed of the ball mill is 100-600 rpm, and the ball milling time is 1-5 h.

[0019] The beneficial effects of the present invention are as follows: the present application utilizes the occupancy and catalytic effect of transition metals, and through a simple solid-phase mixed sintering and crushing method, the transition metals are introduced into the material crystal structure or evenly distributed on the material surface, thereby increasing the utilization rate of transition metals as much as possible, effectively reducing the lithium delithiation potential of lithium-rich compounds, and the synthesis process is simple and controllable. The addition of the ultra-high capacity positive electrode lithium supplement can supplement the loss of active lithium in the lithium-ion battery during the cycle process, and can effectively improve the cycle stability of the lithium-ion battery. .

[0020] The positive electrode lithium replenisher synthesized in the present application has an irreversible capacity of >1000 mAh / g, which is far superior to the existing mature positive electrode lithium replenishers, and can reduce the original 1-5% addition amount of the positive electrode lithium replenisher to 0.5-1%.

[0021] The main body of the positive electrode lithium supplement agent synthesized in the present application is a lithium oxide compounded with a small amount of transition metal compound. The residue content after formation and delithiation is small, and the adverse effect on the energy density and surface and interface stability of the battery system is extremely slight. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is the first charge and discharge specific capacity of Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The following is combined with Figure 1 The present invention is further described in detail with reference to the accompanying drawings and specific embodiments.

[0024] Example 1

[0025] Step S101: Take 2 kg of lithium oxide and mix a specified amount of Li 2 O. Li 6 CoO 4 , Li 5 FeO 4 The initial mixed material was obtained by high-speed mixing at a rotation speed of 2000 rpm for 90 min using a high-speed mixer;

[0026] Step S102: In pure N 2 The initial mixed material was sintered at a high temperature under a molten atmosphere, the sintering temperature was 500°C, and the holding time was 15 hours to obtain a sintered material;

[0027] S103: The sintered material is put into a ball mill for ball milling, with a ratio of 5 mm ball milling beads: 3 mm ball milling beads: 0.5 mm ball milling beads = 1:1:1, and a ratio of ball milling beads to sintered material of 15:1. The ball mill is rotated at 300 rpm for ball milling and milling for 10 hours to obtain a finished product material of the positive electrode lithium supplement agent.

[0028] The obtained finished material was slurried in a glove box, and coated and dried to obtain a positive electrode sheet. After being assembled with a lithium sheet into a button-type half-cell, the charge and discharge capacity test was performed. The sample charging step was 0.1C rate charging to 4.3V. The first charge capacity of the material was 1185.1mAh / g, and the first discharge capacity was 12.27mAh / g. The charge and discharge curves are shown in Figure 1 shown.

[0029] Example 2

[0030] Step S101: Take 3 kg of lithium carbonate and mix a specified amount of Li 2 CO 3 、LiCoO 2 , 30nm Fe 2 O 3 , 20 nm MnO were mixed by a high-speed mixer at a rotation speed of 2000 rpm for 120 min to obtain an initial mixed material;

[0031] Step S102: sintering the initial mixed material at a high temperature of 770° C. in a pure Ar atmosphere for 10 h to obtain a sintered material;

[0032] Step S103: ball milling the sintered material, with a ratio of 5 mm ball milling beads: 3 mm ball milling beads: 1 mm ball milling beads: 0.3 mm ball milling beads = 1:1:1:1, and a ratio of ball milling beads to sintered material of 10:1, and ball milling at a speed of 400 rpm for 12 hours to obtain a finished product material of the positive electrode lithium supplement agent.

[0033] The finished product material was prepared into a slurry in a glove box, and coated and dried to obtain the positive electrode sheet. After being assembled with the lithium sheet into a button-type half-cell, the charge and discharge capacity test was carried out. The sample charging process was 0.1C rate charging to 4.3V, 4.3V constant voltage charging to a current less than 0.02C, and the first charging capacity was 1127.3mAh / g.

[0034] Example 3

[0035] Step S101: Take 2 kg of lithium oxide and mix a specified amount of Li 2 O. Li5 FeO 4 、50nm TiO 2 Mixing with a high-speed mixer at a rotation speed of 1500 rpm for 90 min to obtain an initial mixed material;

[0036] Step S102: In pure N 2 The initial mixed material was sintered at high temperature under the atmosphere, the sintering temperature was 680℃, and the holding time was 15h;

[0037] Step S103: ball milling the sintered material, with a ratio of 3 mm ball milling beads: 1 mm ball milling beads: 0.5 mm ball milling beads = 1:1:1, and a ratio of ball milling beads to sintered material of 10:1, and ball milling at a speed of 200 rpm for 10 hours to obtain a finished product material of the positive electrode lithium supplement agent.

[0038] The finished product material was prepared into a slurry in a glove box, and coated and dried to obtain the positive electrode sheet. After being assembled with a lithium sheet into a button-type half-cell, the charge and discharge capacity test was carried out. The sample charging process was 0.1C rate charging to 4.3V, 4.3V constant voltage charging to a current less than 0.02C, and the first charging capacity was 1095.5mAh / g.

[0039] Example 4

[0040] Step S1: Take 3 kg of lithium hydroxide and add a specified amount of LiOH·H 2 O. Li 5 FeO 4 , 30nm MnO 2 The mixture was mixed by a high-speed mixer at a rotation speed of 2000 rpm for 90 min to obtain an initial mixed material;

[0041] Step S2: In pure N 2 Under the atmosphere, the initial mixed material was sintered at a high temperature of 650°C and the insulation time was 12h. The sintered material was ball-milled at a ratio of 3mm ball milling beads: 2mm ball milling beads: 0.5mm ball milling beads = 1:1:1, and the ratio of ball milling beads to sintered material was 5:1. The ball mill was used for ball milling at a rotation speed of 250rpm. The finished material of the positive electrode lithium supplement was obtained after ball milling for 5h.

[0042] The finished product material was prepared into a slurry in a glove box, and coated and dried to obtain the positive electrode sheet. After being assembled with the lithium sheet into a button-type half-cell, the charge and discharge capacity test was carried out. The sample charging process was 0.1C rate charging to 4.3V, 4.3V constant voltage charging to a current less than 0.02C, and the first charging capacity was 1142.8mAh / g.

[0043] Comparative Example 1

[0044] Step S1: Take 2 kg of lithium oxide and mix a specified amount of Li 2 O, Fe 2 O 3 Mixing with a high-speed mixer at a rotation speed of 2000 rpm for 60 min to obtain an initial mixed material;

[0045] Step S2: In pure N 2 The initial mixed material was sintered at a high temperature of 550°C and a holding time of 15h. 5 FeO 4 The sintered material was ball-milled at a ratio of 3 mm ball milling beads: 2 mm ball milling beads: 0.5 mm ball milling beads = 1:1:1, and the ratio of ball milling beads to sintered material was 5:1. The ball mill was used for ball milling at a speed of 200 rpm. Li 5 FeO 4 Finished product materials of positive electrode lithium supplement.

[0046] The finished product material was prepared into a slurry in a glove box, and coated and dried to obtain the positive electrode sheet. After being assembled with the lithium sheet into a button-type half-cell, the charge and discharge capacity test was carried out. The sample charging process was 0.1C rate charging to 4.3V, 4.3V constant voltage charging to a current less than 0.02C, and the first charging capacity was 796.4mAh / g.

[0047] Table 1: Data comparison table

[0048] sample First charge capacity (mAh / g) Material lithium removal rate (%) Theoretical residue after charging (%) Example 1 1185.1 86.8 25.5 Example 2 1127.3 85.4 34.0 Example 3 1095.5 82.8 26.2 Example 4 1142.8 88.4 28.0 Comparative Example 1 796.4 91.8 51.6

[0049] Table 1 is a comparison of the electrochemical performance data of each embodiment and the comparative example. It can be seen that the positive electrode lithium replenisher prepared according to the method of the present invention has a higher lithium replenishment capacity (>1000mAh / g). Under the same lithium replenishment capacity, compared with the existing traditional commercial mature positive electrode lithium replenisher, the theoretical residue content can be reduced by 60%, which is very suitable for lithium replenishment in the full battery and improving the electrochemical performance of the full battery.

[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any slight modification, equivalent substitution and improvement made to the above embodiment based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing an ultra-high capacity positive electrode lithium supplement, characterized in that: The following steps are involved: S1, mixing, mixing the lithium source and the transition metal compound MO at a high speed in an inert atmosphere in a specified ratio to obtain an initial mixed material; S2, sintering, placing the initial mixed material in an inert atmosphere for high-temperature sintering to obtain a sintered material; S3, ball milling, ball milling the sintered material to obtain a positive electrode lithium supplement.

2. The method for preparing an ultra-high capacity positive electrode lithium supplement according to claim 1, characterized in that: The mixing ratio of the lithium source and the transition metal compound is determined according to the molar ratio of Li in the lithium source and the transition metal M in the transition metal compound, and the molar ratio of Li to the transition metal M is in the range of Li:M=9-25.

3. The method for preparing an ultra-high capacity positive electrode lithium supplement according to claim 1, characterized in that: The lithium source is one or more combinations of Li2O, LiOH·H2O, Li2CO3, LiNO3, and Li2C2O4.

4. The method for preparing an ultra-high capacity positive electrode lithium supplement according to claim 1, characterized in that: M in the transition metal compound is a combination of one or more of Fe, Co, Ni, Mn, Cu and Ti.

5. The method for preparing an ultra-high capacity positive electrode lithium supplement according to claim 5, characterized in that: The transition metal compound MO is a combination of one or more of Li5FeO4, Li2NiO2, Li6CoO4, FeO, Fe2O3, Fe3O4, Co3O4, Co2O3, MnO, MnO2, NiO, and TiO2.

6. The method for preparing an ultra-high capacity positive electrode lithium supplement according to claim 4, characterized in that: The transition metal compound MO is nanometer-sized, and the particle size of the transition metal compound MO is less than 80 nm.

7. The method for preparing an ultra-high capacity positive electrode lithium supplement according to claim 1, characterized in that: The inert gas in steps S1 and S2 is a combination of one or more of Ar, N2, and He.

8. The method for preparing an ultra-high capacity positive electrode lithium supplement according to claim 1, characterized in that: In step S1, a high-speed mixer is used for high-speed mixing operation, the rotation speed of the high-speed mixer is 1500-2500 rpm, and the mixing time is 60-120 min.

9. The method for preparing an ultra-high capacity positive electrode lithium supplement according to claim 1, characterized in that: In step S2, the high temperature sintering temperature is 450-1000° C., and the sintering time is 5-20 hours.

10. The method for preparing an ultra-high capacity positive electrode lithium supplement according to claim 1, characterized in that: In step S1, a ball mill is used for ball milling operation, wherein the ratio of ball milling beads to sintering material in the ball mill is 5:1-20:1; the rotation speed of the ball mill is 100-600 rpm, and the ball milling time is 1-5 hours.

Citation Information

Cited By

  • Positive electrode lithium supplement agent and preparation method and application thereof

    CN120072945A